Time complexity analysis of the binary tree roll algorithm - Bozhinovski, Adrijan; Tanev, George; Stojchevska, Biljana; Pachovski, Veno; Ackovska, Nevena (My University, 2016)
This paper presents the time complexity analysis of the Binary Tree Roll algorithm. The time complexity is analyzed theoretically and the results are then confi rmed empirically. The theoretical analysis consists of fi nding recurrence relations for the time complexity, and solving them using various methods. The empirical analysis consists of exhaustively testing all trees with given numbers of nodes and counting the minimum and maximum steps necessary to complete the roll algorithm. The time complexity is shown, both theoretically and empirically, to be linear in the best case and quadratic in the worst case, whereas its average case is shown to be dominantly linear for trees with a relatively small number of nodes and dominantly quadratic otherwise.
Keywords: Binary Tree Roll Algorithm, time complexity, theoretical analysis, empirical analysis